Investimento em infraestrutura portuária: Uma análise da exportação de soja no Terminal de Grãos do Maranhão - PINHEIRO, Jailson Silva (2018)
The present study aims to discuss the investment made at the Maranhão Grain Terminal. The theories of economic development and the strategies to reach it are approached. The relationship between investment in public and private infrastructure in the four modalities: road, air, rail and port is analyzed. The port of Itaqui is described its characteristics, its forms of access, its cradles and its investment. As an investment, the TEGRAM project based on the TCU Judgments nº 2,073 / 2011 and 1,838 / 2013, aims to provide access to: the objective of this investment; to the calculation used to substantiate this objective; the projection of cargo handling; the minimum contractual movement and the fixed and variable installments paid by the concessionaire. In view of this information, a detailed analysis of the investment is carried out. Finally, it is inferred that the investment has not reached its objective until the moment, so that it is verified that the EVTE and the projection have flaws.